Correction: Kannampuzha et al. A Systematic Role of Metabolomics, Metabolic Pathways, and Chemical Metabolism in Lung Cancer. Vaccines 2023, 11, 381 - Sandra Kannampuzha; Anirban Goutam Mukherjee; Uddesh Ramesh Wanjari; Abilash Valsala Gopalakrishnan; Reshma Murali; Arunraj Namachivayam; Kaviyarasi Renu; Abhijit Dey; Balachandar Vellingiri; Harishkumar Madhyastha; Raja Ganesan (Vaccines)
Following the publication of paper [...]